The Impact of Total Qualıty Management on Patıent Satısfactıon: A Fıeld Study in the Health Centers of the Syrıans in Gazıantep - Prof. Dr. Abdulkadir BİLEN; Ahmet SITKI (Journal of Arts & Social Sciences, 2020)
Total Quality Management (TQM) is a major concern in business organizations and especially in the healthcare sector. The TQM philosophy focuses on the customer and focuses on how can the organization meets the customer's needs and wants, as well as the need to integrate activities within the organization. TQM focuses on continuous improvement of all aspects of the organization and on highlighting the excellence of all employees in the organization, with all management principles to manage jobs with few errors and low costs from start to finish. The aim of this research in the health sector is about patient’s satisfaction in the health sector represented by these TQM’ indicators (top management commitment, benchmarking, customer satisfaction, employee’s satisfaction, continuous improvement). This included the impact of total quality management factors on patients’ satisfaction.